1992
DOI: 10.4294/jpe1952.40.57
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Numerical Modeling of Surface-Wave Propagation in a Sedimentary Basin.

Abstract: The characteristics of the long-period ground motion with a period range from 2 to 20 s observed in the southwestern Kanto district, Japan, are discussed. Dispersive wave trains are found in seismograms observed during a moderate earthquake near the Izu-Oshima Island. The observed group velocities are in good agreement with the ones calculated for Love wave in subsurface structures derived from seismic refraction work in the area. It is interpreted that the Love wave radiated from the source is amplified, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This ambiguity of interpretation may come from the fact that the earthquakes used were shallow. Yamanaka et al (1989Yamanaka et al ( , 1992 found Love waves with a period range between 5 and 10 s in linear array data in the southern Kanto basin from group velocity analyses and interpreted them as basin-transduced waves from two-dimensional numerical simulations, though they did not determine the arrival directions of the Love waves.…”
Section: Introductionmentioning
confidence: 99%
“…This ambiguity of interpretation may come from the fact that the earthquakes used were shallow. Yamanaka et al (1989Yamanaka et al ( , 1992 found Love waves with a period range between 5 and 10 s in linear array data in the southern Kanto basin from group velocity analyses and interpreted them as basin-transduced waves from two-dimensional numerical simulations, though they did not determine the arrival directions of the Love waves.…”
Section: Introductionmentioning
confidence: 99%
“…Axisymmetric calculations take only the same memory and computational time as (2, 2) calculations. Yuan et al (1986) and Yamanaka et al (1992) applied axisymmetric finite difference methods, and Sato and Hasegawa (1990) proposed an axisymmetric finite element method combined with a thin layer element method. Kohketsu (1987) and Baba (1989) developed axisymmetric versions of the Rayleigh-Fourier method, where Baba (1989) used the Laplace transform instead of the Fourier transform.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (1986) simulated the 3-dimensional strong motions observed during the Nov. 15, 1976 Ninghe, China earthquake (M=6.4) by use of an axisymmetric finite difference method incorporating a faulting model. Yamanaka et al (1992) also used an axisymmetric finite difference method to model Love-wave propagation in the Kanto plain, Japan.…”
Section: Interior Methodsmentioning
confidence: 99%
“…Later Phases at Station HNG Several researchers (e.g., Yamanaka et al, 1992;Kato et al, 1993;Hisada et al, 1993) investigated ground-motion characteristics observed at sites in the Tokyo metropolitan area from the shallow Izu earthquakes (Fig. lb) and pointed out that observed surface waves from the hu earthquakes are strongly affected by near-source heterogeneity in a Quaternary basin in Sagami Bay (Nishizawa et al, 1996).…”
Section: Estimation Of Source Model By Grid-search Technique Using Bo...mentioning
confidence: 99%